Relatório do produto (guia ilustrado digital “causas precisam causar”) - Gouvêa, Veronica de Jesus Marques Pierre de (2018)
The present academic work aims to contribute on Experience Economy and Creative Economy fields by proposing a specific dialogue on the modeling of experiences that mix forms, functions and emotions. It also proposes reflections on the use of creativity and innovation as guides for acting and generating impacts for causes. The work also presents theoretical references from Experience Economy and Creative Economy, fields that had supported the creation of think-live-feel method for development of interactive, sensorial and emotional experiences based on three assumptions: explaining dense themes and technical or academic information, especially scientific or social researches, in experiences promotes new reflections and learning; developing unprecedented and surprising experiences from translated information leads to the promotion of new and intense experiences; propitiating unexpected feelings can allow causes to generate reflections and promote new attitudes in individuals. This work also brings results of pilot application of the method and knowledge obtained